Pengaruh Environmental Performance Terhadap Environmental Disclosure dan Economic Performance (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar Di BEI) - Dedi Putra; Indah Lutfia Utami (Jurnal Akuntansi, 2017)
Abstract This study was aimed at demonstrating empirically the Influence of Environmental Performance on Environmental Disclosure and Economic Performance. The dependent variables in this research were the Environmental Disclosure and Economic Performance, while the independent variable was the Environmental Performance. The data collection method used purposive sampling. The study sample was ten mining companies listed on the Indonesia Stock Exchange and had a PROPER rate from the Ministry of Environment in 2011-2015. The data used in this research was secondary data. The data was analyzed using simple regression, Eviews ver 4.1. The results showed that the Environmental Performance significantly influence Environmental Disclosure and Economic Performance. Keywords:   Environmental Performance, Environmental Disclosure, Economic  Performance